A Kárpát-medence tájhasználati rendszere a 18. században - Frisnyák, Sándor (Közép-Európai Közlemények, 2015)
The land-use system of the Carpathian Basin, which developed after the Hungarian conquest, radically changed during the Ottoman rule in the 16th and 17th centuries. The cultural landscape and its settlement network in the central plains and hills (Ottoman Hungary accounted for 1/3 of Hungary’s total area) were mostly destroyed. The land-use of areas surrounding Ottoman Hungary, such as Western-Transdanubia, Upper Hungary, and Transylvania, became more intensive, because of the population increase due to the refugees coming from the Hungarian Great Plains and the settlers from abroad. After one-and-a-half-century of Ottoman rule, a state of almost continuous wars, and following Rákóczi’s War of Independence (1703-1711) there began the reconstruction and repopulation of the country, and the reorganization of economic life. The basic structure of the land-use of the Carpathian Basin had evolved by the end of the Árpád Age, which served as a basis for the land-use systems of later ages, like the 18th-century reconstruction of the cultural-landscape and regional development. The study outlines the land-use changes, anthropogenic landscape formation, and the formation of economic space, by showing the characteristic land-use systems of the plains, hills and mountains.